2022
DOI: 10.1002/smll.202202642
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insights into the Self‐Assembly of Block Copolymer Suckerin Polypeptides into Nanoconfined β‐Sheets

Abstract: Suckerin in squid sucker ring teeth is a block‐copolymer peptide comprised of two repeating modules—the alanine and histidine‐rich M1 and the glycine‐rich M2. Suckerin self‐assemblies display excellent thermo‐plasticity and pH‐responsive properties, along with the high biocompatibility, biodegradability, and sustainability. However, the self‐assembly mechanism and the detailed role of each module are still elusive, limiting the capability of applying and manipulating such biomaterials. Here, the self‐assembly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 81 publications
0
15
0
Order By: Relevance
“…Besides, we have calculated the probabilities of β-sheet oligomer size and β-sheet size of PHF6 in two systems. Here, the β-sheet oligomer size is defined by the total number of β-strands in a β-sheet oligomer, and β-sheet size refers to the number of strands in an n -stranded β-sheet. , It can be seen from Figure d that PHF6 predominantly aggregates into oligomers with the number of β-strands of 4–8, and the large size (9–10) of β-sheet oligomers can also be observed in the PHF6 system. When Y310 is phosphorylated, the probability of β-sheet oligomers with four β-strands is obviously increased, and the large size of β-sheet oligomers is disappeared.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, we have calculated the probabilities of β-sheet oligomer size and β-sheet size of PHF6 in two systems. Here, the β-sheet oligomer size is defined by the total number of β-strands in a β-sheet oligomer, and β-sheet size refers to the number of strands in an n -stranded β-sheet. , It can be seen from Figure d that PHF6 predominantly aggregates into oligomers with the number of β-strands of 4–8, and the large size (9–10) of β-sheet oligomers can also be observed in the PHF6 system. When Y310 is phosphorylated, the probability of β-sheet oligomers with four β-strands is obviously increased, and the large size of β-sheet oligomers is disappeared.…”
Section: Resultsmentioning
confidence: 99%
“…A H-bond was considered to be formed if the distance between the H-bonding donor D and the acceptor A was less than 0.35 nm and the angle of D–H···A was greater than 150°. Following our previous studies, the average β-sheet size was weighed according to the size of each β-sheet. , The potential of mean force (PMF) was constructed using the equation F = − RT ln P ( x , y ), where P ( x , y ) is the probability of a conformation having a certain value of two selected reaction coordinates x and y . The Daura analysis method was applied to cluster the sampled conformations using a Cα root-mean-square deviation (Cα-rmsd) cutoff of 0.45 nm .…”
Section: Methodsmentioning
confidence: 99%
“…475,477 SAXS studies 434 further indicated that the randomly oriented β-sheets of SRT are organized at the next hierarchical level into a hexagonally packed nanofibrillar lattice, as illustrated in Figure 10D-v. Using all atom discrete MD (DMD) simulations, Ding and co-workers 478,479 later confirmed the self-assembly of the [M1-M2] block copolymer architecture of suckerins, in particular corroborating that [M1] modules formed cross-β oligomers whereas [M2] modules exhibited a stronger self-assembly propensity but remained largely unstructured. These computational studies led the authors to propose a refined self-assembly model of suckerins driven by microphase separation between [M1] and [M2] modules, with [M2] acting as molecular glue and confining the β-sheet-rich [M1] modules into amyloid-like nano-assemblies.…”
Section: Gxxxxxxxdengxxxxxxfyxadgnxxxgfyxapxxxxxxmentioning
confidence: 87%
“…(i) The short peptide A1H1 can be self-assembled into stiff mesoscale fibers (left, reproduced with permission from ref . Copyright 2017 American Chemical Society) made of amyloid-like cross-β nanofibrils as predicted by MD simulations (right, reproduced from ref . Creative Commons CC BY-NC 4.0.…”
Section: Bioengineering Of Protein-based Materialsmentioning
confidence: 99%
“…Furthermore, rigorous statistical mechanics theory can be applied to relate the ensemble of microscopic configurations with macroscopic thermodynamic properties. Classical molecular simulations have been applied to study a wide range of biomaterial systems such as supramolecular biopolymer, DNA-based bioconjugate, self-assembling peptides, carbohydrate-based biomaterials, , and lipid membranes. …”
Section: Methodsmentioning
confidence: 99%